The space privatization : the forming process of social space in kampung, Prawirotaman, Yogyakarta - Tika Ainunnisa Fitria,; Mohd Hisyam Rasidi,; Ismail Said, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Prawirotaman is an urban village called kampung that has changed into a tourist village since the 1980s. Tourism development has evoked changes in social spaces and the community. There has been a phenomenon of territorial deprivation leading to the privatization of space. Hence, this research used a qualitative approach to identify how the privatization of space influenced the forming of social spaces within the kampung. Data were collected through observation and interviews to understand the transformation of social space and residents’ social activities changes. These methods were conducted in the afternoon or after Asr prayer until before Maghrib prayer, focusing on transition areas. Next, the analysis used behaviour mapping assisted by ArcGIS to show the nodes of residents' social activities and visual-spatial analysis to understand the transformation of social spaces. This research resulted that the space privatization impacted the forming of kampung social spaces that were influenced by 1) residents' daily movement, 2) connectivity and openness of the transition area, 3) gathering habits, and 4) availability of social space in the transition area. The space privatization did not reduce residents' opportunities for social activities; nevertheless, it stimulated residents to form their social spaces continuously. The research found the important factors that form social space in the urban village. The finding also contributed to sustaining the urban villages, particularly those that have transformed into tourist villages.